Synthesis and structure–activity relationships of pyrazine-2-carboxamide derivatives as novel echinoderm microtubule-associated protein-like 4 (EML4)–anaplastic lymphoma kinase (ALK) inhibitors. Issue 8 (15th April 2019) - Iikubo, Kazuhiko; Kurosawa, Kazuo; Matsuya, Takahiro; Kondoh, Yutaka; Kamikawa, Akio; Moritomo, Ayako; Iwai, Yoshinori; Tomiyama, Hiroshi; Shimada, Itsuro
Graphical abstract: Abstract: Echinoderm microtubule-associated protein-like 4 (EML4)– anaplastic lymphoma kinase (ALK) is a valid therapeutic target for the treatment of EML4– ALK-positive non-small cell lung cancer (NSCLC). We discovered12c as a novel and potent EML4– ALK inhibitor through structural optimization of5a . In mice xenografted with 3T3 cells expressing EML4–ALK, oral administration of12c demonstrated potent antitumor activity. This article describes the synthesis and biological evaluation of pyrazine-2-carboxamide derivatives along with studies of their structure– activity relationship (SAR) using computational modeling.